The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/ese3.1027
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of the non‐Newtonian fracturing fluid influences on the fracture propagation

Abstract: Hydraulic fracturing fracture propagation is the main factor affecting the fracturing effect. In view of the more diversified selection of fracturing fluid, the problem of fracture propagation in non-Newtonian fluid fracturing is often encountered in fracturing. In this paper, the influencing factors of fracture propagation of non-Newtonian fluid fracturing fluid are analyzed. Based on PKN model, a threedimensional fracture propagation model considering the rheology and filtration of fracturing fluid is establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 40 publications
(5 reference statements)
0
6
0
Order By: Relevance
“…Entering the 21st century, with the rapid development of computer technology and numerical calculation methods, numerical simulation methods have become an important tool in engineering practice and become an important method in the study of shale reservoir fracturing engineering. Currently, the numerical simulation methods used for the study of hydraulic fracture propagation mechanism in the shale fracturing process are finite element method, extended finite element method, discrete element method, boundary element method, phase field method, and other methods [2,13,14,32,63,[69][70][71][82][83][84]. Among them, the first four are commonly used methods, while the phase field method is an emerging method that needs to be further studied, and based on these numerical methods, some models were established, such as the finite element model, extended finite element model, discrete fracture model, displacement discontinuity model, unconventional fracture model, etc.…”
Section: Numerical Simulation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Entering the 21st century, with the rapid development of computer technology and numerical calculation methods, numerical simulation methods have become an important tool in engineering practice and become an important method in the study of shale reservoir fracturing engineering. Currently, the numerical simulation methods used for the study of hydraulic fracture propagation mechanism in the shale fracturing process are finite element method, extended finite element method, discrete element method, boundary element method, phase field method, and other methods [2,13,14,32,63,[69][70][71][82][83][84]. Among them, the first four are commonly used methods, while the phase field method is an emerging method that needs to be further studied, and based on these numerical methods, some models were established, such as the finite element model, extended finite element model, discrete fracture model, displacement discontinuity model, unconventional fracture model, etc.…”
Section: Numerical Simulation Methodsmentioning
confidence: 99%
“…Among them, geological factors [2,[56][57][58][59][60] are determined by the nature of the shale itself, mainly the mineral composition of the shale, rock mechanical parameters, natural fractures, laminae surfaces, interseam interference, and ground stress. Engineering factors [11,[61][62][63][64], on the other hand, are due to the influence of the artificially selected fracturing process during the extraction of shale gas, mainly the fracturing fluid, construction displacement, injection pressure and injection rate, and other factors. Both geological and engineering factors have a certain influence on fracture propagation, so when studying the mechanism of fracture extension, each influencing factor should be considered comprehensively to determine the degree of influence of each factor, clarify the main controlling factors of fracture propagation and achieve accurate prediction of fracture extension.…”
Section: Introductionmentioning
confidence: 99%
“…Their research found that rocks with high brittleness mineral content are more likely to form X-shear and network fracture patterns, while rocks with low brittleness mineral content are more prone to form simple shear fracture patterns . Young’s modulus and Poisson’s ratio have a significant impact on the fracture width and total fracture area, showing a positive correlation with the fracture height. , The mineral type influences the magnitudes of Young’s modulus and Poisson’s ratio. The correlation between Poisson’s ratio and quartz and pyrite is the strongest.…”
Section: The Influence Of Geological Factors On Fracture Propagationmentioning
confidence: 99%
“…Simulating HF propagation in the formation is a challenge, with at least three physical processes to be coupled simultaneously: (a) fracture initiation and propagation 12 ; (b) fluid flow within the fracture 13 ; (c) rock deformation due to fluid pressure on the fracture surface 14 ; with the upgrading of computer hardware, many new methods and models have been proposed to solve the numerical solution of complex coupled equations and thus capture the dynamic interaction process between HF and NF. An extended finite element method (XFEM)-based flow formulation was proposed by Shi and colleagues, [15][16][17][18] and the computer programs they prepared were able to simulate the interaction between HF and NF.…”
Section: Introductionmentioning
confidence: 99%